PERSPEKTIF SOSIAL DAN TEKNIS PENANGKAPAN BENIH IKAN KUWE (Caranx sp) DI TELUK AMBON - Jacobus Wilson Mosse; Barbara Grace Hutubessy; Julian; Darlin Darlin (Universitas Mataram, 2024)
Juvenile Trevallies (Caranx sp) fishing provides superior natural seeds for fish farmers using floating cages. Seeds from nature have a lower mortality rate than from hatcheries, but the activity of fishing and availability of natural seeds has not been a scientific concern. We tried to involve in the process of juveniles trevallies fishing in Ambon bay and interviewed fishers who caught the fish aiming to learn their fishing technique to catch juvenile trevallies, map the fishing ground of Caranx sp in Ambon Bay, and analyze the catches based on social and technical perspectives. Data collection was carried out from May to July 2022. Direct interviews were conducted to respondents from Galala Village, Ambon Municipality. The respondents were fishers who captured juvenile trevallies as seeds, so we could be able to participate in their fishing trips. Respondents were consisted of junior to senior fishers and varied in fishing experience. Since the floating cages were operated at Ambon Bay, the fishing on juvenile trevallies have been started around 2013. Seagrass beds in the inner part of Ambon Bay are the habitats for juvenile trevallies. The small size of juveniles is more abundant than the bigger fish, and the average catch during 5-years interval increased slowly. Based on the social and technical perspective, the practice of juvenile trevallies fishing is categorized as sustainable fishing due to the proportional harvesting to the population productivity. Maintaining trevally population in Ambon Bay, its biological perspctives should be continuedly studied.